2021
DOI: 10.7759/cureus.15709
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Histoplasmosis in an Adult With Rheumatoid Arthritis Not on Biological Immune Modulators

Abstract: Histoplasmosis is a fungal disease caused by a dimorphic fungus known as Histoplasma capsulatum (H. capsulatum), which is endemic to areas around river valleys and southeastern states in the United States (US). Patients with histoplasmosis are asymptomatic, and the condition is usually diagnosed by an incidental finding of a pulmonary granuloma on a chest radiograph. In rare cases, this disease can develop into a progressive disseminated form and cause fatal and diffuse pulmonary infiltrates in immunocompromis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We found 1159 studies and included 108 manuscripts published between 1962 and 2022, totaling 298 patients 7–10,12–115 . We excluded 38 articles that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…We found 1159 studies and included 108 manuscripts published between 1962 and 2022, totaling 298 patients 7–10,12–115 . We excluded 38 articles that could not be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…It is equally possible, that patients might have been exposed to fomites contaminated with the conidia of H. capsulatum in the environment from which they contracted the disease. Nega et al [20] and Avasthi et al [21] have reported that fomites contaminated with the conidia of H. capsulatum can cause any infection if an individual is exposed.…”
Section: Discussionmentioning
confidence: 99%